Analyzing Figurative Language and Writer’s Emotion in Paul Mauriat’s Love is Blue - Aldha Williyan; Retno Purwani Sari; Nessa Yuanita; Riksan Nawawi Fahrul Padri (Journal on Education, 2023)
Songwriters utilize figurative language to portray their ideas, sentiments, and emotions in a manner that is more intriguing, attractive, and distinctive. This encourages this research to study a song written by Paul Mauriat entitled "Love is Blue." This song is analyzed to answer some research objectives, namely what figurative languages are frequently used by the writer, how the contextual meaning is built, and what emotions are expressed by the writer. Through the analysis, this present study finds five types of figurative language in this song with different percentages. With 38% of the total, metaphor dominates the use of figurative language. The rest of the figurative language found in this study consists of alliteration (33%), hyperbole (11%), repetition (11%), and personification (7%). Also, there are three basic emotions that are found in every context of the lyrics that indicate the use of figurative language. Those are the emotions of sadness, anger, and happiness. The findings indicate that the use of figurative language can express various types of emotions.